2013
DOI: 10.1073/pnas.1301365110
|View full text |Cite
|
Sign up to set email alerts
|

Ocean acidification alters the otoliths of a pantropical fish species with implications for sensory function

Abstract: Ocean acidification affects a wide diversity of marine organisms and is of particular concern for vulnerable larval stages critical to population replenishment and connectivity. Whereas it is well known that ocean acidification will negatively affect a range of calcareous taxa, the study of fishes is more limited in both depth of understanding and diversity of study species. We used new 3D microcomputed tomography to conduct in situ analysis of the impact of ocean acidification on otolith (ear stone) size and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 32 publications
(49 reference statements)
3
91
1
Order By: Relevance
“…We conducted five factorial experiments to evaluate the sensitivity of M. menidia early life traits to high (2000-2800 µatm) and extreme CO 2 conditions (4000-6200 µatm) across four temperatures (17,20,24, and 28 • C) that encompassed contemporary and potential future conditions in nearshore silverside spawning habitats. The experiments showed few significant CO 2 effects on response traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted five factorial experiments to evaluate the sensitivity of M. menidia early life traits to high (2000-2800 µatm) and extreme CO 2 conditions (4000-6200 µatm) across four temperatures (17,20,24, and 28 • C) that encompassed contemporary and potential future conditions in nearshore silverside spawning habitats. The experiments showed few significant CO 2 effects on response traits.…”
Section: Discussionmentioning
confidence: 99%
“…The latter has been particularly well documented for marine fish, where adults are largely tolerant of acute high-CO 2 levels far exceeding predicted OA conditions [9,10]. By contrast, fish early life-stages (embryos and early larvae) that are still developing effective acid-base regulation have exhibited reduced survival [11,12], reduced growth [13,14], defective development [14,15], otolith over-calcification [16,17], and behavioral abnormalities in response to high-CO 2 conditions Table 1. Summary of five CO 2 × temperature experiments on M. menidia offspring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in otolith size in relation to increases in CO 2 was found in temperate fish such as sea bass larvae (Checkley et al 2009), newly hatched herring larvae (Franke and Clemmesen 2011), juvenile walleye pollock (Hurst et al 2012), and cod larvae (Maneja et al 2013b) as well as in tropical fish such as clownfish larvae (Munday et al 2011b) and cobia (Bignami et al 2013b). A change in otolith size and density may affect the auditory sensitivity and perception in the larvae (Bignami et al 2013a). Sensory and cognitive impairment in respect to homing behavior (Munday et al 2009b, Devine et al 2011, prey detection (Cripps et al 2011), predator avoidance , and risk assessment (Ferrari et al 2012) has been observed in coral reef fishes and has been linked to effects of CO 2 on neurotransmitter functions in the brain (Nilsson et al 2012).…”
Section: Figmentioning
confidence: 96%
“…But differences in the reaction to OA are not only found in the extent but also the mode of reaction to OA between species. Bignami et al (2013a) predict differences in the sound reception in cobia larvae based on an otolith hearing model, whereas behavioral studies performed on larval Atlantic cod using swimming kinematics have shown that Atlantic cod larvae seem rather resilient to increased pCO 2 , despite a significant difference in otolith growth (Maneja et al 2013a, b). Further studies should be performed using older fish and applying the behavioral approaches used for coral reef fish.…”
Section: Figmentioning
confidence: 99%